2015
DOI: 10.12968/joan.2015.4.3.131
|View full text |Cite
|
Sign up to set email alerts
|

Social pressures and health consequences associated with body hair removal

Abstract: The removal of body hair on the legs, arms and pubic area is commonplace in today's society and being hair-free is associated with beauty and femininity. Not only do adult women feel pressure from their peers and partners to achieve the hairless ideal, but also girls as young as 11 years old are presenting to health professionals with no pubic hair. Heidi Williamson looks hair removal practices in the Western world

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Further, the costs of hair removal continue to have little impact on women’s choices. These costs are not only financial, but are evidenced in the increase in hair removal related injuries over time, particularly to the groin area, and rising viral infections such as molluscum contagiosum (Williamson, 2015). Despite these contradictions, choice, and taking individual responsibility for those choices, remains the dominant explanatory framework for the beauty practices women engage in (Stuart & Donaghue, 2012).…”
mentioning
confidence: 99%
“…Further, the costs of hair removal continue to have little impact on women’s choices. These costs are not only financial, but are evidenced in the increase in hair removal related injuries over time, particularly to the groin area, and rising viral infections such as molluscum contagiosum (Williamson, 2015). Despite these contradictions, choice, and taking individual responsibility for those choices, remains the dominant explanatory framework for the beauty practices women engage in (Stuart & Donaghue, 2012).…”
mentioning
confidence: 99%
“…Along these lines, our results showed that societal and gender norms were the main reasons for women's PHR, specifically and very significantly, the partners' preferences (even constituting an indispensable requirement) and hygiene. Regarding the fashion of hair removal practices in Western society, Williamson [49] highlighted the potential negative consequences of PHR on health.…”
Section: Discussionmentioning
confidence: 99%
“…Many sources offer commentary on pubic hair, often featuring information about how to groom or eliminate it. Many imply that pubic hair grooming is a matter of personal preference in the absence of scant information about potential health consequences related to various methods of removal (DeMaria et al 2014;Williamson 2015). These deserve more than a mere mention, again, couched in neutral, non-alarmist language.…”
Section: Concerning Genital Appearancementioning
confidence: 99%